Grafts of orange (Citrus sinensis) and mandarin (Citrus reticulata) in production phase - Pérez-Macias, Mercedes; Soto, Enio; León-Pacheco, Rommel Igor; Rodríguez-Yzquierdo, Guastavo Adolfo; Villagrán-Munar, Edwin Andrés (Agronomía Mesoamericana, 2021)
Introduction. In Venezuela, citrus is the fifth most important fruit crop, with a harvested area of 18,084 ha, and an average yield of 14.2 t ha-1, below world production. Despite this, there is little information on the physiology and agronomy of the grafting of the most commonly used citrus cultivars in the country, as part of a strategy to select the best combinations (graft/rootstock) and the most limiting seasons for crop production. Objective. To evaluate agronomic and physiological levels of five citrus cultivars during the period 2013-2015. Materials and methods. A trial was carried out on citrus plants sown between the period of January 2013 and August 2015 at the National Center for Agricultural Research, Maracay, Venezuela, in three replications under a completely randomized design, to evaluate variables associated with gas exchange and crop phenology in five cultivars of the most important citrus fruits of Venezuela. Results. 1) Citrus trees showed partial opening of the stomata due to high temperature and drought without causing decrease in photosynthetic rate. 2) The plants with the highest average values in the gas exchange variables in the graft (Cleopatra and Volk) and in the rootstock (Dancy during the driest periods and Valencia in the wettest periods) caused the Cleopatra-Dancy, Cleopatra-Valencia, Volk-Valencia, and Volk-Dancy combinations to achieve the highest photosynthetic yield during all evaluation periods. 3) The budding phenological stage in citrus plants were the most important sink sources for the net photosynthetic assimilation rates. Conclusions. The cultivar Cleopatra-Dancy had the most stable behavior for variables associated with gas exchange and Volk-Dancy for producing in drier seasons.